Genetic polymorphism related to ethambutol outcomes and susceptibility to toxicity - Barliana, Melisa Intan; Afifah, Nadiya Nurul; Yunivita, Vycke; Ruslami, Rovina (Frontiers in Genetics, 2023)
The World Health Organization (WHO) stated that ensuring access to effective and optimal treatment is a key component to eradicate tuberculosis (TB) through the End TB Strategy. Personalized medicine that depends on the genetic profile of an individual is one way to optimize treatment. It is necessary because of diverse drug responses related to the variation in human DNA, such as single-nucleotide polymorphisms (SNPs). Ethambutol (EMB) is a drug widely used as the treatment for Mycobacterium Tuberculosis (Mtb) and/non-tuberculous mycobacteria and has become a potential supplementary agent for a treatment regimen of multidrug-resistant (MDR) and extensively drug-resistant (XDR) TB. In human genetic polymorphism studies of anti-tuberculosis, the majority focus on rifampicin or isoniazid, which discuss polymorphisms related to their toxicity. Whereas there are few studies on EMB, the incidence of EMB toxicity is lower than that of other first-line anti-TB drugs. To facilitate personalized medicine practice, this article summarizes the genetic polymorphisms associated with alterations in the pharmacokinetic profile, resistance incidence, and susceptibility to EMB toxicity. This study includes 131 total human studies from 17 articles, but only eight studies that held in the low-middle income country (LMIC), while the rest is research conducted in developed countries with high incomes. Personalized medicine practices are highly recommended to maintain and obtain the optimal therapeutic effect of EMB.